Computed Tomographic Tenography of Normal Equine Digital Flexor Tendon Sheath: An Ex Vivo Study - Luca Lacitignola; Pasquale De Luca; Alessandro Guarracino; Antonio Crovace (Veterinary Medicine International)
Aim of this study was to document the normal computed tomographic tenography findings of digital flexor tendon sheath. Six ex vivo normal equine forelimbs were used. An axial approach was used to inject 185 mg/mL of iopamidol in a total volume of 60 mL into the digital flexor tendon sheaths. Single-slice helical scans, with 5 mm thickness, spaced every 3 mm, for a pitch of 0.6, and with bone algorithm reconstruction, were performed before and after injections of contrast medium. To obtain better image quality for multiplanar reconstruction and 3D reformatting, postprocessing retroreconstruction was performed to reduce the images to submillimetre thickness. Computed tomographic tenography of digital flexor tendon sheaths could visualize the following main tendon structures for every forelimb in contrast-enhanced images as low densities surrounded by high densities: superficial digital flexor tendon, deep digital flexor tendon, manica flexoria, mesotendons, and synovial recess. Results of this study suggest that computed tomographic tenography can be used with accuracy and sensitivity to evaluate the common disorders of the equine digital flexor tendon sheath and the intrathecal structures.